PHYSIOLOGY AS THE THYORETICAL BASIS OF MEDICINE - Yu. E. Vagin (Сеченовский вестник, 2013)
This paper deals with the problem of basic role of physiology in medical activity. The physiology description and directions of its development are presented. The history of physiology development is observed, especially Russian school of physiology. The thoughts of the great physiologists (Georg Prochaska, Claude Bernard, Ivan Sechenov, Ivan Pavlov, Pyotr Anokhin, Konstantin Sudakov) about the basic role of physiology for the medicine are analyzed. In addition, physiological mechanisms of relationship between a doctor and a patient are described. All mentioned lead to the conclusion that the physiology gives not only theoretical knowledge about the clinical medicine, but also the philosophic basis for the medical activity in general.